Study on nanoparticles of Aloe vera extract on growth performance, survival rate and body composition in Siberian sturgeon (Acipenser baerii) - Sharif Rohani, M.; Haghighi, M.; Bazari Moghaddam, S. (2017)
The application of nanotechnology in drug delivery and a variety of supplements is very impressive. In this regard, the use of this knowledge can be effective in the performance of medicinal plants in aquaculture. In the present study Aloe vera was extracted and its nanoparticles were produced. Three levels of Aloe vera nanoparticles in Siberian sturgeon (Acipenser baerii) were evaluated for the effects on growth performance, survival rate and body composition. A total of 360 Siberian sturgeon (A. baerii) with an average of 10.95 ± 0.04 (g) randomly divided into four treatment groups with three replicates each. The treatment groups were fed with diets that included 0% (control), 0.5, 1 and 1.5% of Aloe vera nanoparticles for 60 days. Weight gain, initial body weight, condition factor, feed conversion ratio, specific growth rate, protein efficiency ratio, survival rate, and body composition (protein, lipid, carbohydrate, ash and moisture) were measured and compared among the fish in the different groups. The results showed that growth indices of fish fed the Aloe vera nanoparticles were higher than the control diet, so that the difference between the control group and 1% Aloe vera nanoparticles was more than that in other treatments. In each of the body composition parameters, no significant differences were observed among the treatments and control groups (p>0.05). Considering that there are no significant differences in results between 1% and 1.5% Aloe vera nanoparticles, the results showed that adding 1% Aloe vera nanoparticles to the fish diet improves the growth factors of Siberian sturgeon. Published